Summer Intensive on Community-Engaged Scholarship: Generative Tensions and Future Directions for Professional Development - Diane M. Doberneck (The University of Alabama, 2022)
Since the mid-1990s, universities and colleges have sought to institutionalize service-learning and community engagement. Along with aligning institutional roles and rewards, professional development for faculty and academic staff has been a key strategy for institutionalization. However, as Welch and Plaxton-Moore (2017) noted, professional development around community engagement is rarely guided by theory or conceptual frameworks and often lacks impact or outcome data. As a response to this critique, this paper presents Michigan State University's Summer Intensive on Community-Engaged Scholarship, a weeklong professional development program for faculty, academic staff, and advanced graduate students offered in person annually. The author describes the program's underlying conceptual framework, chronicles iterative improvements in its implementation over 4 years, and documents its impacts on 85 participants. The most significant gains in participant understanding were in history and foundations, variations of community engagement, collaboration techniques, use of theory, conceptual frameworks and best practices to guide community-engaged research or teaching and learning, communicating with public audiences, communicating with academic audiences, and preparing materials for reappointment, promotion, and tenure. The author concludes with reflections on the program's inherent generative tensions and suggests future directions for professional development related to community-engaged scholarship and practice.